Examining the Relevance of T-CRM and H-CRM for the Bank-Customer Partnership Quality and Willingness to Invest More - Rimbasari, Ana; Wijaya, Nikodemus Hans Setiadi (Universitas Muhammadiyah Yogyakarta, 2020)
The current study examines the use of technology and human in Customer Relationship Management (CRM), especially in the banking industry. We analysed whether human still plays a role in the relationship in this industry. The purpose of this work is to determine the role of technology (T-CRM) and human (H-CRM) in enhancing partnership quality and customer behaviour (i.e., willingness to invest more). We collected data by distributing online questionnaires. The respondents were the customers of Bank Mandiri, Bank Central Asia (BCA), and Bank Rakyat Indonesia (BRI), who have experienced in using both technology-based and human-based banking services.Â A total of 161 responses were used in our data analysis. The results demonstrated that T-CRM and H-CRM had positive effects on partnership quality. It was found that partnership quality has a positive effect on willingness to invest more. This research advises that T-CRM is needed in the banking industry, but technology cannot replace the benefits of humans. Technology and people based relationship are both still needed to improve the relational quality between the service providers (banks) and their customers.